Kraft Lignin: From Pulping Waste to Bio‐Based Dielectric Polymer for Organic Field‐Effect Transistors. (31st October 2022) - D'Orsi, Rosarita; Irimia, Cristian Vlad; Lucejko, Jeannette J.; Kahraman, Bilge; Kanbur, Yasin; Yumusak, Cigdem; Bednorz, Mateusz; Babudri, Francesco; Irimia‐Vladu, Mihai; Operamolla, Alessandra
Abstract: Lignin is an abundant biopolymer deriving from industrial pulping processes of lignocellulosic biomass. Despite the huge amount of yearly produced lignin waste, it finds scarce application as a fine material and is usually destined to be combusted in thermochemical plants to feed, with low efficiency, other industrial processes. So far, the use of lignin in materials science is limited by the scarce knowledge of its molecular structure and properties, depending also on its isolation method. However, lignin represents an intriguing feedstock of organic material. Here, the structural and chemical‐physical characteristics of two kraft lignins, L1 and L2, are analyzed. First, several molecular characterization techniques, such as attenuated total reflectance ‐ Fourier transform infrared spectroscopy, elemental analyses, gel permeation chromatography, evolved gas analysis‐mass spectrometry, UV–vis, 31 P‐ and 13 C‐ nuclear magnetic resonance spectroscopies are applied to get insights into their different structures and their degree of molecular degradation. Then, their efficient application as gate dielectric materials is demonstrated for organic field‐effect transistors, finding the increased capacity of L1 with respect to L2 in triggering functional and efficient devices with both p‐type and n‐type organic semiconductor molecules. Abstract : Kraft lignin is applied as the gate dielectric layer in C60 or pentacene organic field‐effect transistors. The role of lignin molecular degradation and functional groups is elucidated.